Polypeptide-Based Systems: From Synthesis to Application in Drug Delivery - Mariia Stepanova; Alexey Nikiforov; Tatiana Tennikova; Evgenia Korzhikova-Vlakh (Pharmaceutics, 2023)
Synthetic polypeptides are biocompatible and biodegradable macromolecules whose composition and architecture can vary over a wide range. Their unique ability to form secondary structures, as well as different pathways of modification and biofunctionalization due to the diversity of amino acids, provide variation in the physicochemical and biological properties of polypeptide-containing materials. In this review article, we summarize the advances in the synthesis of polypeptides and their copolymers and the application of these systems for drug delivery in the form of (nano)particles or hydrogels. The issues, such as the diversity of polypeptide-containing (nano)particle types, the methods for their preparation and drug loading, as well as the influence of physicochemical characteristics on stability, degradability, cellular uptake, cytotoxicity, hemolysis, and immunogenicity of polypeptide-containing nanoparticles and their drug formulations, are comprehensively discussed. Finally, recent advances in the development of certain drug nanoformulations for peptides, proteins, gene delivery, cancer therapy, and antimicrobial and anti-inflammatory systems are summarized.